Savings, Investment, and Growth in Mexico : Five Years After the Crisis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Despite Mexico's recent remarkable progress in adjusting its fiscal and external accounts and in restructuring its economy, the recovery of growth has remained elusive. This paper reviews some aspects of Mexico's recent performance and suggests that systemic adjustment uncertainty, and policy conflicts between stabilization and real depreciation objectives, are among the factors that have contributed most to delaying the private sector's investment response and preventing a sustainable recovery. The paper also assesses future growth prospects and resource mobilization needs, based on a growth model that fully incorporates the internal transfer problem and emphasizes solvency requirements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet